Mechanisms for the Modulation of Dopamine D(1) Receptor Signaling in Striatal Neurons - Nishi, Akinori (Frontiers Research Foundation, 2011)
In the striatum, dopamine D(1) receptors are preferentially expressed in striatonigral neurons, and increase the neuronal excitability, leading to the increase in GABAergic inhibitory output to substantia nigra pars reticulata. Such roles of D(1) receptors are important for the control of motor functions. In addition, the roles of D(1) receptors are implicated in reward, cognition, and drug addiction. Therefore, elucidation of mechanisms for the regulation of dopamine D(1) receptor signaling is required to identify therapeutic targets for Parkinson’s disease and drug addiction. D(1) receptors are coupled to G(s/olf)/adenylyl cyclase/PKA signaling, leading to the phosphorylation of PKA substrates including DARPP-32. Phosphorylated form of DARPP-32 at Thr34 has been shown to inhibit protein phosphatase-1, and thereby controls the phosphorylation states and activity of many downstream physiological effectors. Roles of DARPP-32 and its phosphorylation at Thr34 and other sites in D(1) receptor signaling are extensively studied. In addition, functional roles of the non-canonical D(1) receptor signaling cascades that coupled to G(q)/phospholipase C or Src family kinase become evident. We have recently shown that phosphodiesterases (PDEs), especially PDE10A, play a pivotal role in regulating the tone of D(1) receptor signaling relatively to that of D(2) receptor signaling. We review the current understanding of molecular mechanisms for the modulation of D(1) receptor signaling in the striatum.